Selective In Silico Antiplatelet Evaluation of Maerua Oblongifolia Phytocompounds Targeting GPIIB/IIIA (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Cardiovascular diseases remain one of the leading causes of mortality worldwide, with platelet aggregation playing a pivotal role in thrombus formation and vascular occlusion. Although several antiplatelet drugs are clinically available, their use is often associated with adverse effects including bleeding complications, drug resistance, and variable patient responses. Therefore, the identification of safer and more effective antiplatelet agents from natural sources has become an important area of research. The present study aimed to investigate the antiplatelet potential of phytochemicals derived from Maerua oblongifolia through an in silico drug discovery approach. A total of 168 compounds identified through GC-MS analysis were screened, and nine compounds were selected based on structural diversity and reported biological activities. Molecular docking studies were performed against two major platelet aggregation targets, namely the P2Y12 receptor (PDB ID: 4NTJ) and GPIIb/IIIa integrin (PDB ID: 3FCS). Further evaluation included interaction analysis, virtual screening, ADMET profiling using SwissADME, and toxicity prediction using ProTox-III. Among the screened compounds, Sarreroside exhibited the strongest binding affinity towards GPIIb/IIIa integrin (-7.511 kcal/mol), followed by Guanosine (-6.973 kcal/mol) and Xanthosine (-6.052 kcal/mol). Interestingly, none of the compounds demonstrated significant interactions with the P2Y12 receptor. ADMET and toxicity analyses indicated favorable pharmacokinetic properties and acceptable safety profiles for the lead compounds. These findings suggest that Maerua oblongifolia contains promising phytochemicals capable of selectively inhibiting GPIIb/IIIa-mediated platelet aggregation and may serve as valuable lead molecules for future antithrombotic drug development.
Keywords: Maerua oblongifolia; Antiplatelet activity; GPIIb/IIIa integrin; P2Y12 receptor; Molecular docking; ADMET; Sarreroside